Planktonic foraminifera in biostratigraphy and biochronology - Petrizzo, Maria Rose; King, David J.; Pearson, Paul N.; Huber, Brian T.; Wade, Bridget S. (Newsletters on Stratigraphy, 2025)
Planktonic foraminifera, single-celled protists, are extensively used in biostratigraphy and biochronology thanks to their abundance in marine sediments, widespread distribution and extensive fossil record in the Cretaceous and Cenozoic. We present an overview of planktonic foraminiferal taxonomy, and evolutionary trends that are relevant to the practice and application of biostratigraphy. Additionally, we present the key features in planktonic foraminiferal paleoecology and paleogeography that characterise Cretaceous-Cenozoic species diversity and geographic distributions. The types of bioevents and biozone definitions, morphologic terminology and species identification in evolutionary lineages are illustrated through examples. Planktonic foraminifera are crucial in the development of geological timescales and their value and reliability in chronostratigraphic correlations is demonstrated by the identification of 14 primary and secondary boundary events applied in the definition of the Global Stratotype Section and Points (GSSP). The presentation of the methodologies used in biochronological studies is aimed to describe the significance of planktonic foraminifera for correlation and integration with magnetostratigraphy, chemostratigraphy and orbital tuning. Calibration difficulties such as diachroneity of species occurrences are discussed, and examples of astronomical calibrations are provided for the Late Cretaceous and Late Miocene.